The European snow vole (Chionomys nivalis) in Ukraine: a species in the far northeast of its distribution - Barkaszi, Z. (Theriologia Ukrainica, 2019)
The European snow vole is a widespread rodent species of Europe having a highly fragmented range and a number of isolated populations. The species’ distribution is mainly restricted to high mountains of Europe and Asia Minor. The European snow vole is represented in the mammal fauna of Ukraine by an isolated population in the subalpine zone of the Carpathians. An extensive survey of all collection samples of the species deposited in zoological museums of Ukraine was conducted, including analysis of 149 available specimens. The paper presents a review of all known records of the species in Ukraine with an updated map of distribution. Morphological features of the local isolated population belonging to the subspecies C. n. ulpius is also presented with a focus on external and craniometrical features of adult specimens. The European snow vole is a rather large rodent compared to other vole species of the local fauna. No sex-related variation by linear body dimensions was revealed in adult specimens of the species. Analysis of craniometrical characters and its comparison with that of two other subalpine vole species (Microtus agrestis and Terricola subterraneus) showed a substantial distinctness of the European snow vole, which might be related to existing niche differentiation between the three vole species supporting stability and low trophic and spatial competition within the subalpine rodent complex. The current state of the local snow vole population along with the specifics of its habitat preferences in the Ukrainian Carpathians are discussed with particular attention on its role in the local subalpine small mammal community as an indicator species. The abundance of the species in the Ukrainian Carpathians is quite high within the species’ key habitats. In particular, the European snow vole dominated in samples trapped in all types of plant associations of the Chornohora massif. As an endemic and relict species with a restricted distribution, the European snow vole is protected in Ukraine and listed as vulnerable in the Red Data Book of Ukraine. Current conservation issues are discussed along with possible measures necessary for sustainable development of the Ukrainian snow vole population. Снігурка альпійська, або полівка снігова, є широко розповсюдженим видом гризунів, що характеризується суттєво фрагментованим ареалом та наявністю кількох ізольованих популяцій. Поширення виду в основному обмежене високогірними районами Європи та Малої Азії. У теріофауні України снігурка альпійська представлена ізольованою популяцією в субальпійському поясі Українських Карпат. Проведено детальний огляд колекційних зразків виду, що зберігаються у п’ятьох зоологічних музеях України, — це 149 доступних для дослідження зразків. Представлено результати перегляду усіх відомих знахідок в Україні з оновленою мапою поширення виду. Показано морфологічні особливості місцевої ізольованої популяції, що належить до підвиду C. n. ulpius з акцентом на екстер’єрних та краніометричних ознаках дорослих особин. Снігурка альпійська має досить великі розміри порівняно з іншими видами полівок місцевої фауни. За лінійними ознаками тіла не виявлено значних відмінностей між дорослими особинами самок і самців. Аналіз краніометричних ознак та їх порівняння з такими у двох інших субальпійських видів полівок (Microtus agrestis та Terricola subterraneus) показав суттєву відмінність снігурки альпійської. Така мінливість може бути пов’язаною з диференціацією цих видів за окремими компонентами екологічної ніші, що у свою чергу підтримує стабільність та низький рівень трофічної і просторової конкуренції всередині субальпійського родентокомплексу. Показано сучасний стан локальної популяції снігурки альпійської та особливості біотопної приуроченості виду в Українських Карпатах з увагою на його роль як індикаторного виду. Чисельність снігурки альпійської в Українських Карпатах порівняно висока у межах притаманних їй біотопів. Зокрема, вид домінував у відловах у всіх типах рослинних асоціацій Чорногірського масиву. Як ендемічний і реліктовий вид з обмеженим поширенням, снігурка альпійська в Україні охороняється і включена до Червоної книги і має статус «вразливий». Обговорено проблеми охорони виду з можливими заходами задля збереження популяції виду в Україні.